THE ENVIRONMENT: CHALLENGES AND THE PATH TOWARD SUSTAINABILITY - Rakhmonova Zebokhon,; Qandiyorova Aziza, (TADQIQOTLAR, 2026)
Abstract: This article presents a comprehensive exploration of the environment and the urgent necessity to protect it in the modern era. Recent research, literature, and global activities show an increasing understanding of the complex relationship between human  civilization  and  natural  systems.  The  work  dives  deep  into  the  issues  of environmental  degradation,  climate  change,  the  role  of  education  and  public awareness, as well as practical pathways toward sustainable future development.